Rehabilitation of post-stroke patients - L. B. Novikova; A. P. Akopyan; K. M. Sharapova (Лечащий Врач, 2021)
In the neurorehabilitation department of the hospital of Ufa Emergency care, there were 98 patients after ischemic stroke were treated. The use of complex multidisciplinary and individualized methods of rehabilitation can significantly increase the effect of rehabilitation activities and improve the quality of life of patients.